Measurement of Machine Effectiveness Using the Overall Equipment Effectiveness (OEE) Value Approach on the BX-75 Machine (A Case Study) - Indro Prakoso; Denny Andiya Nur Wibowo (Journal of Industrial Engineering and Halal Industries, 2023)
PT XYZ is a company engaged in the pipe industry with various types of HDPE pipe products according to consumer needs. PT XYZ has problems with the BX-75 engine because it has a high breakdown value and is obtained from historical production data. The high breakdown caused the production process of the BX-75 engine to be hampered and the daily production target was reduced. To determine the effectiveness of the BX-75 engine, measurements using the Overall Equipment Effectiveness (OEE) method are needed. The research was conducted using the OEE method to identify whether it is in accordance with world class standards, if the OEE value is still low, a Six Big Losses analysis will be carried out from the pareto chart which will determine what losses affect the low OEE value and analyze the details of the causes of each fishbone diagram. The average OEE value on BX-75 machines in November-December 2022 was 78.86%. The result is still below 85% so six big losses analysis is still needed. There are two types of losses that dominate, namely downtime losses and setup & adjustment losses. Downtime losses have an average loss of 13.50% and setup losses have an average of 9.53%.